Emergent ecological dynamics in videogames: What player paratexts reveal - May, Lawrence (Eludamos: Journal for Computer Game Culture, 2025)
Videogames invite players to inhabit virtual worlds that often represent or simulate ecologies. Existing conceptual frameworks for understanding these dynamics and experiences as they arise from play emphasise the role of the videogame text in structuring such meaning. This article introduces the concept of emergent ecological dynamics to explain how, within the situated and ephemeral experience of playing a videogame, new ecocritical meaning can emerge, and can be captured in user-created paratexts. Undertheorised in ecocritical game studies are player experiences of ecologies and environments that emerge in ways unanticipated and unintended by gamemakers. By drawing on explanations of assemblage, emergence, and the materiality of digital media, this article suggests a latent potential for all videogame texts to convey ecocriticality. The methodological value of addressing player paratexts—as a means for scholars to access and analyse otherwise transitory emergent ecological dynamics—is also explored. The capacity of such user-created artefacts to manifest players’ revelations of ecological entanglement, development of ecological awareness and encounters with potent sensations of affect drawn upon as examples.
Keywords: ecocriticism; videogame ecologies; player paratexts; emergence; assemblage